Status Hukum Donor ASI Anonim dalam Era Modern - Muhammad Fikri Akbari (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
This study aims to analyze the legal status of anonymous breast milk donors in the perspective of Islamic law and Indonesian positive law in the modern era. The main focus of this study is to understand how the practice of breast milk donation carried out without the identity of the donor can raise legal issues related to nasab, mahram relationships, and legal protection for recipients and donors. The type of research used is library research with a normative legal approach. This approach is used to examine various legal sources and relevant literature, such as shar'i texts, classical and contemporary fiqh books, laws and regulations, as well as the results of previous studies that discuss anonymous donor ASI and the concept of raḍa'ah in Islamic law. This research is descriptive-analytical in nature, with the aim of systematically describing phenomena and critically analyzing rational and contextual legal arguments. The results show that the practice of anonymous breast milk donation has humanitarian value and health benefits, but has the potential to cause nasab confusion and a vacuum of legal norms in Indonesian positive law. From the perspective of Maqashid Sharia, this practice can be seen as a form of tahqiq al-maslahah in the health sector, but still requires strict and transparent regulation to be in line with the principles of benefit, legal certainty, and family protection in Islamic law